Idiopathic Inflammatory Myopathies - Dimachkie, Mazen M.; Barohn, Richard J. (Seminars in Neurology, 2012)
The idiopathic inflammatory myopathies are a group of rare disorders including polymyositis (PM), dermatomyositis (DM), and autoimmune necrotizing myopathies (NMs). The idiopathic inflammatory myopathies share many similarities. They present acutely, subacutely, or chronically with marked proximal and symmetric muscle weakness, except for associated distal and asymmetric weakness in inclusion body myositis. The idiopathic inflammatory myopathies also share a variable degree of creatine kinase (CK) elevation and a nonspecifically abnormal electromyogram demonstrating an irritative myopathy. The muscle pathology demonstrates inflammatory exudates of variable distribution within the muscle fascicle. Despite these similarities, the idiopathic inflammatory myopathies are a heterogeneous group. The overlap syndrome (OS) refers to the association of PM, DM, or NM with connective tissue disease, such as scleroderma or systemic lupus erythematosus. In addition to elevated antinuclear antibodies (ANA), patients with OS may be weaker in the proximal arms than the legs mimicking the pattern seen in some muscular dystrophies. In this review, we focus on DM, PM, and NM and examine current and promising therapies.
Keywords: myositis; polymyositis; dermatomyositis; necrotizing myopathy